Tinjauan Yuridis Perlindungan Data Pribadi Terhadap Risiko Kebocoran Data Pribadi Saat Transaksi Pembayaran Digital - Angelita Pinondang Manurung, Evelyn; Osmunda Eawea Monny, Maria (Shofanah Media Berkah, 2025)
Nowadays, the development of digital technology is increasingly showing a trend of digital payment transactions. The more payment transactions are carried out using digital methods, the greater the risk that threatens user privacy, namely personal data leakage. The vulnerability of personal data to the risk of being leaked to irresponsible parties can occur, especially when users make digital payment transactions. Of course, this risk results in financial losses and loss of consumer trust. Currently, Indonesia has a legal umbrella regarding personal data protection, namely the Personal Data Protection Law. But it is undeniable that various violations of personal data leakage also threaten user privacy. This study aims to determine the effectiveness of policies or legal regulations for personal data protection as a legal umbrella against the risk of data leakage during digital payment activities. This study uses a normative legal research method using legal sources of literature and related literature.